Mechanical properties of Bacillus subtilis cell walls: effects of removing residual culture medium. - Thwaites, J J (1991)
Experiments are described in which the tensile strength, the initial (Youngs') modulus, and other mechanical properties of the bacterial cell wall were obtained as functions of relative humidity (RH) in the range of 20 to 95%. These properties were deduced from tensile tests on bacterial thread, a fiber consisting of many highly aligned cells of Bacillus subtilis, from which residual culture medium had been removed by immersion in water. Reasons are given to support the idea that the mechanical properties of bacterial thread relate directly to those of the cylinder wall and that they are not influenced by septa, cytoplasm, or the thread assembly. The data show that the cell wall, like many other heteropolymers, is visco-elastic. When dry, it behaves like a glassy polymer with a tensile strength of about 300 MPa and a modulus of about 13 GPa. When wet, its behavior is more like a rubbery polymer with a tensile strength of about 13 MPa and a modulus of about 30 MPa. Thus, the cell wall is stronger than previously reported. Walls of this strength would be able to bear a turgor pressure of 2.6 MPa (about 26 atm). The dynamic behavior suggests a wide range of relaxation times. The way in which mechanical behavior depends strongly on humidity is discussed in terms of possible hydrogen bond density and the ordering of water molecules. Cell walls in threads containing residual culture medium TB are, except at low RH, 10 times more flexible and about 4 times less strong. All of their mechanical properties appear to vary with change in RH in a manner similar to those of walls from which the culture medium has been washed, but with a downshift of about 18% RH.